PEMBELAJARAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS 5 SEKOLAH DASAR MENGGUNAKAN MEDIA ULAR TANGGA BERKARTU DI MASA PANDEMIC COVID-19 MELALUI PEMBELAJARAN DARING - Sylvia Rabbani; Multia Mudrika Tussa'adah; Reka Bismihani Novriyanti (Jurnal Ilmiah P2M STKIP Siliwangi, 2021)
The background of this research is the low understanding ability of elementary students, especially in mathematics. This is accompanied by a lack of interactive mathematics learning media that can facilitate children in learning mathematics in a fun and meaningful way. For this reason, it is very important to improve the understanding ability of elementary school students by creating and implementing interactive mathematics learning media. Media made from simple but meaningful materials to make students more familiar with the mathematics material being taught. We can also apply this in online learning during the Covid-19 pandemic. The long-term objective of this research program is to develop innovative learning through the preparation of Cardboard Snakes and Ladders learning media for mathematics learning in grade 5 elementary schools. Specifically, the specific targets to be achieved are as follows: (1).Improve the ability of 5th grade students to understand mathematics through the application of Carded Ladder Snake Media. (2). Compilation of Cardboard Snake and Ladder Learning Media for Mathematics learning. (3) Compilation of Teaching Materials based on Carded Ladder Snake Media. The research method is descriptive qualitative method. Learning was carried out online during the Covid-19 pandemic. The research instrument used wasWritten test with indicators of mathematics comprehension ability and teacher and student observation sheets.